Bread and bullets - George A. Akerlof; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2016)
Standard economics omits the role of narratives (the stories that people tell themselves and others) when they make all kinds of decisions. Narratives play a role in understanding the environment; focusing attention; predicting events; motivating action; assigning social roles and identities; defining power relations; and establishing and conveying social norms. This paper describes the role narratives play in decision making, as it also juxtaposes this description against the backdrop of the Bolshevik-spawned narrative that played a critical role in the history of Russia and the Soviet Union in the 20th Century.
Keywords: A12; A13; A14; D03; D04; D20; D23; D30; D62; D71; D72; D74; E02; E03; 330; narrative; motivation; attention; prediction; identity; social assignment